Darwin Koenig letter to Thomas Kent regarding bird sightings, December 3, 1980 - Koenig, Darwinet al (1980)
Darwin Koenig provides an annotated list of birds sighted around Montezuma and Allamakee County. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed